PENGARUH MODEL CONTEXTUAL TECHING AND LEARNING (CTL) BERBANTUAN MEDIA WORDWALL TERHADAP HASIL BELAJAR MATA PELAJARAN IPAS SISWA KELAS IV GUGUS 4 KECAMATAN PANJI - Wachadania, Putri; Amroellah, Afif; Bramantha, Heldie (CENDEKIA PENDIDIKAN, 2025)
This research is based on the lack of variation in the learning process in schools, which has an impact on the low learning outcomes of students in science subjects. The aim of this research is to find out how the CTL model assisted by Wordwall media has an impact on learning outcomes for science subjects in class IV Gugus 4 Panji District. This research is a quasi-experimental research. The research population consisted of 24 students from class 4 of SD Negeri 4 Curah Jeru as the experimental class and 24 students from class 4 of SD Negeri 1 Tenggir as the control class. Samples were collected by means of research data obtained through student learning outcomes tests. The proposed hypothesis was tested using the t-test, with results of Tcount 39.1 and Ttable 2.013. Ho was rejected. Based on this data, it can be concluded that the learning outcomes of students taught using the CTL model assisted by wordwall media are not comparable to the learning outcomes of other students. who were taught without the CTL model assisted by language media.